2022
DOI: 10.3389/fimmu.2022.1041233
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of neoadjuvant immunotherapy in resectable esophageal or gastroesophageal junction carcinoma: A pooled analysis of prospective clinical trials

Abstract: Neoadjuvant chemoradiotherapy (NCRT) plus radical esophagectomy is currently the standard treatment for resectable esophageal or gastroesophageal junction (GEJ) carcinoma. The aim of this study is to evaluate the efficacy and safety of neoadjuvant immunotherapy in resectable esophageal or GEJ carcinoma. Prospective clinical trials investigating efficacy and/or safety of neoadjuvant immunotherapy with immune checkpoint inhibitors (ICIs) followed by radical esophagectomy in patients with newly diagnosed resectab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Анализируя проспективные исследования, изучающие присоединение моноклональных антител в неоадъювантном режиме пациентам с тримодальной терапией, Zhu J. et al (2022) показали, что иммунотерапия значимо не улучшает частоту полных патоморфологических ответов при плоскокле-точном раке пищевода, но приводит к увеличению частоты нежелательных явлений 3-4 степени [37].…”
Section: возможности адъювантной терапии и внедрение иммунотерапииunclassified
“…Анализируя проспективные исследования, изучающие присоединение моноклональных антител в неоадъювантном режиме пациентам с тримодальной терапией, Zhu J. et al (2022) показали, что иммунотерапия значимо не улучшает частоту полных патоморфологических ответов при плоскокле-точном раке пищевода, но приводит к увеличению частоты нежелательных явлений 3-4 степени [37].…”
Section: возможности адъювантной терапии и внедрение иммунотерапииunclassified
“…43.2% of patients even reached pCR. With the arrival of the immune era, several studies on the treatment of locally advanced esophagus cancer with neoadjuvant chemotherapy combined with immunotherapy or chemoradiotherapy combined with immunotherapy also showed good [8][9][10][11][12][13][14][15][16][17][18][19][20] prospect. In the TD-NICE study [8] , tislelizumab + albumin paclitaxel + carboplatin were used as a neoadjuvant therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent systematic review including 27 phase 2 or 3 clinical trials with 815 patients, the pooled pathological complete response (pCR) rate was 32.4% in ESCC after neoadjuvant chemoimmunotherapy(nCIT), with the pooled incidence of treatment-related severe adverse events of 26.9% (7). Zhu et al reported that neoadjuvant immunochemoradiotherapy could not improve the pCR rate than neoadjuvant chemoradiotherapy (nCRT) for ESCC, but significantly increased the risk of severe adverse events (8). Another multicenter retrospective study that included 370 ESCC patients showed that the pCR rates of mono-immunotherapy, nCIT, and nCRT plus immunotherapy were 12.1%, 25.5%, and 42.3%, respectively (9).…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al. reported that neoadjuvant immunochemoradiotherapy could not improve the pCR rate than neoadjuvant chemoradiotherapy (nCRT) for ESCC, but significantly increased the risk of severe adverse events ( 8 ). Another multicenter retrospective study that included 370 ESCC patients showed that the pCR rates of mono-immunotherapy, nCIT, and nCRT plus immunotherapy were 12.1%, 25.5%, and 42.3%, respectively ( 9 ).…”
Section: Introductionmentioning
confidence: 99%